Excusable and compensable delays in the construction of building project – A study in the states of Selangor and Wilayah Persekutuan Kuala Lumpur , Malaysia. - Mohammed Alias, Yusof; Noraziah, Mohammad; Zulhairuse, Mat Derus (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/